Jathil Lanang And Social Identity - Cahyo Nugroho, Oki; Pinaryo, Pinaryo; Wahyu Tricana, Deny (Jogjakarta Communication Conference (JCC), 2023)
The style of performance Reyog Ponorogo is quite distinctive and distinct from other dance presentations. Jathil dancers are among the significant performers in reyog performances, particularly in reog in the form of reyog obyogan. The cavalry dancers in the Reyog mythological epic had a very distinct paradigm throughout their journey. The Jathil dancers were initially portrayed by male actors who embodied the Gemblak stereotype. Then, between the late 1980s and the early 1990s, they transformed into the female Jathil dancers that are so common in today's Reyog performances. “Jathil lanang”, or male dancers, have, however, reemerged in the last two years and have become a distinct-phenomena with the same model and still holding onto the same form and dancing technique as the previous reyog. With a qualitative descriptive study approach, photographic media is employed to express the visual identity of jathil lanang. The findings of this study suggest that the jathil lanang dancers are transitioning from a social identity in the past to a professional identity in the present.